The Ideological Transformation And Fragmentative-Ambiguity of Global Salafism - Rizqa Ahmadi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
Global salafism is a new issue compared to salafism in a simple sense. Initially salafism is not as massive as it has been symptomatic in these last years. His movement remains a embodiment among intellectuals and the Islamic movement observers. From the previously documented study of literature and research data, it shows that global salafism is a dynamically transformed movement. Starting from the purification of Islamic teachings to fragmented into various branches and streams. This deversification marks global salafism as an ambiguous and fragmentative movement. Ambiguous because it is inconsistent on one type of doctrine, even in the same source they are fighting for a truth claim. While called fragmentative because the movement is fragmented into various colors so it is not easy to recognize it for sure.